Assessing tenant health amid social housing redevelopment: lessons from a pilot project - Christopher M Standen; Erica McIntyre; Hazel Easthope; Jennifer Green; Fiona Haigh (Sax Institute, 2023)
Objectives: To trial methods for a future longitudinal study to: a) assess how the redevelopment of a large social housing estate affects the health of tenants; and b) act on health needs identified throughout the redevelopment. Type of program or service: Self-reported health assessment with referral to community-based link worker. Methods: Participants recruited from the tenant population completed (online or face-to-face) a health questionnaire covering self-reported health status and behaviours, housing conditions, sense of community, and demographics. Those identified as being at moderate/high risk of psychological distress and/or alcohol use disorder were contacted by a community-based link worker, who connected them with health/human services as appropriate. Results: A total of 24 tenants were recruited for the pilot study against a target sample size of 50. The health questionnaire and referral process worked as expected, with no issues reported. Lessons learnt: This pilot study successfully trialled methods for: a) assessing tenants' health; and b) referring those identified as being likely to have unmet health service needs to a community-based link worker, leveraging existing collaborations between academics, the local health district and community groups. Fewer tenants than expected, and none aged younger than 35 years, participated in the survey. Furthermore, the substantial number of suspicious/fraudulent responses was not anticipated. Recruitment and data collection approaches must be reviewed to address these issues if this study is to be scaled up. Although only a pilot project, we connected several tenants who had unmet health needs with a health service. While it is impossible to generalise from our small sample, the number of referrals (one-quarter of participants) indicates a potentially large unmet need for health services in the community. It highlights the importance of link workers or other person-centred integrated care interventions in social housing populations.